Varroa Volatiles Offer Chemical Cues to Honey Bees for Initial Parasitic Recognition - Qinglong Zhao; Xinning Wang; Ahsan Mustafa; Ying Wang; Hongfang Wang; Xuepeng Chi; Baohua Xu; Zhenguo Liu (Biomolecules)
Olfaction mediated by the antennae is a vital sensory modality for arthropods and could be applied as a tool in pest control. The ectoparasitic mite Varroa destructor poses a significant threat to the health of the honey bee Apis mellifera worldwide and has garnered global attention. To better understand the chemical ecology of this host–parasite relationship, we collected and characterized the volatile organic compounds (VOCs) from V. destructor and used electroantennography (EAG) to record the responses of honey bee (A. c. cerana and A. m. ligustica) antennae to the different VOCs. Fifteen VOCs were detected from V. destructor using gas chromatography–mass spectrometry (GC-MS), which mainly contained ethyl palmitate, followed by isoamyl alcohol, nonanal, and ethyl oleate. The EAGs for ethyl palmitate were higher at the lowest stimulus loading (5 μg/μL in liquid paraffin) in A. c. cerana compared to A. m. ligustica, suggesting that A. c. cerana may have acute sensitivity to low concentrations of some VOCs from V. destructor. After exposure to ethyl palmitate for 1 h, the relative expression levels of AcerCSP1 and AcerOBP21 in A. c. cerana significantly increased, as well as the level of AmelCSP1 in A. m. ligustica, while AmelOBP8 showed no significant changes. The results indicate that the EAG response was influenced by the VOC composition and concentration. A. c. cerana tended to be more responsive than A. m. ligustica to the VOCs of V. destructor. Our findings offer a deeper understanding of how bees recognize V. destructor, potentially using ethyl palmitate as a chemical cue.